Master Data Management Maturity Model (MD3M) Assessment: Case Study of PT Graha Segara - Farhan Setya Dhitama; Imairi Eitiveni; Nilamsari Putri Utami (International Journal Labs, 2025)
This study focuses on assessing the maturity level of Master Data Management (MDM) implementation at PT Graha Segara, a service provider in the logistics industry, with a particular focus on data inconsistencies resulting from manual container data management. MDM plays a critical role in ensuring data consistency, quality, and integrity, which are essential for efficient operations. The study utilizes the Master Data Management Maturity Model (MD3M) to evaluate the current state of MDM practices within the company and identifies key challenges, including the impact of data inconsistencies on billing processes and the obstacles to effective data integration at container terminals. The results of the research highlight how manual data entry errors create inefficiencies, disrupt business processes, and delay critical operations. By assessing the company's current MDM maturity, this study aims to provide a comprehensive understanding of the issues at hand and offers strategic recommendations to improve the implementation of MDM. These recommendations are designed to enhance the quality and consistency of data, streamline operations, and improve overall operational efficiency. Ultimately, this research will contribute to the development of a more reliable data management system, enabling PT Graha Segara to optimize its business processes and better support the company’s growth and customer satisfaction.